AUTHOR INDEX/INDEX ONOMASTIOUE - Anttila, Eric; Anand, Havelin; Baldwin, Paul E.; Ball, Alan J. S.; Bassett, Betty A.; Beardlsey, Barbara; Beaumont, Jane; Beaumont, Jane; Blouin-Cliche, Odette; Bozyk, Patricia; Brandreth, Michael; Brearley, Neil; et al. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF